The Teachers' Selection of The Use of Learning Management Systems in Teaching and Learning - Siscka Elvyanti; Yadi Mulyadi; Iwan Kustiawan (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2022)
The selection of a website as a reference for learning directly affects the quality of information for the person who accesses it. The objectives and expected results of the learning management system depend on the quality of the teaching process and its effectiveness in online access. This research is expected to support teachers who carry out the teaching and learning process virtually during the pandemic. The research method used is quantitative, with a descriptive approach for evaluating, ranking, and choosing the learning management system. Based on the research survey, the criteria for analysis of the LMS platforms in this paper are summarized in three categories: learning skills tools, communication within LMS tools, and ease of use tools. The main goal is to present a comparative analysis of 5 electronic learning management systems. From the teachers' view in this research, only one LMS supports all three categories. The critical criteria of LMS are supported by video conference, chat room for personal discussion, and simple to use.